An examination of internet and land-based gambling among adolescents in three Canadian provinces: results from the youth gambling survey (YGS) - Tara Elton-Marshall; Scott T. Leatherdale; Nigel E. Turner (BMC, 2016)
Abstract Background With the rapid proliferation of new gambling technology and online gambling opportunities, there is a concern that online gambling could have a significant impact on public health, particularly for adolescents. The aim of this study is to examine online and land-based gambling behaviour among adolescents in 3 Canadian provinces (Ontario, Newfoundland and Labrador, Saskatchewan) prior to the implementation of legalized online gambling. Methods Data are from 10,035 students in grades 9 to 12 who responded to the 2012-2013 Youth Gambling Survey (YGS) supplement, a questionnaire administered as part of the Canadian Youth Smoking Survey (YSS, 2012) in 3 provinces: Newfoundland and Labrador (n = 2,588), Ontario (n = 3,892), and Saskatchewan (n = 3,555). Results Overall, 41.6 % of adolescents (35.9 % of females and 47.4 % of males) had gambled in the past 3 months. 9.4 % of adolescents had gambled online in the past 3 months alone (3.7 % of females and 15.3 % of males). The most popular form of online gambling was online sports betting. Adolescents also engaged in online simulated gambling including internet poker (9.1 %) and simulated gambling on Facebook (9.0 %). Few adolescents participated in online gambling exclusively and online gamblers were more likely than land-based gamblers to engage in multiple forms of gambling. A higher proportion of adolescent online gamblers scored "high" or "low to moderate" in problem gambling severity compared to land-based only gamblers. Conclusions Despite restrictions on online gambling at the time of the study, adolescents were engaging in online gambling at a significantly higher rate than has been previously found. Adolescents were also using technology such as video games to gamble and free online gambling simulations.